Double activation of the geminal carbon−hydrogen bonds in 1,3-butadiene by a diiridium complex - Ristic Petrovic, Dusan; Torkelson, Jeffrey R.; Hilts, Robert; McDonald, Robert; Cowie, Martin (My University, 2000)
The binuclear complex [Ir2(CH3)(CO)2(dppm)2][CF3SO3] (1) (dppm = Ph2PCH2PPh2) reacts with 1,3-butadiene at ambient temperature over a 48 h period to give the vinylvinylidene-bridged product [Ir2(CH3)(H)(CO)2(μ-H)(μ-CC(H)C(H)CH2)(dppm)2][CF3SO3] (2). At −55 °C the same reactants yield the 1,3-butadiene adduct [Ir2(CH3)(CO)2(μ-η2:η2-H2CC(H)C(H)CH2)(dppm)2][CF3SO3] (3), in which the diolefin binds in an s-trans geometry on one face of the complex. A proposal is advanced rationalizing the conversion of 3 to 2 upon warming.
Keywords: Transition metals; Butadiene; Metals; Hydrocarbons; Ligands